Determinan biopsikososial kebugaran kardiorespirasi pada penderita diabetes melitus (jemaah haji) - Ekawati, Puspaningdyah; Setiani, Onny; Sutiningsih, Dwi; Suroto, Suroto; Fauzi, Muh (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2024)
Background: Diabetes Mellitus (DM) is closely related to decreased cardiorespiratory fitness and impaired exercise. DM is the second highest disease after hypertension in Hajj pilgrims in Blora Regency. The cardiorespiratory fitness status of Hajj pilgrims in Blora Regency in 2023 was mostly in the sufficient category (49.6%) and the poor category (30.4%). Given the importance of cardiorespiratory fitness in Hajj pilgrims with DM, an approach is needed that is able to examine various factors related to cardiorespiratory fitness through a biopsychosocial approach. Purpose: To analyze the biopsychosocial determinants of cardiorespiratory fitness in Hajj pilgrims with DM. Method: A cross-sectional design study was used to examine biopsychosocial factors on cardiorespiratory fitness. This study was conducted in Blora Regency in February-April 2024. The sampling technique used purposive sampling, the sample size was calculated using the Slovin formula and based on the researcher's justification, a sample of 119 respondents was taken. The inclusion criteria were being able to communicate well, being diagnosed with DM by a doctor, and laboratory results (GDS, GDP and HBA1c). Data analysis used univariate, bivariate (chi-square and logistic regression), and multivariate. Results: Most respondents (47.1%) had poor cardiorespiratory fitness (not fit). The results of the bivariate test showed that the variables of age (p=0.035, PR= 1.57), gender (p=0.044, PR= 1.56), BMI (p=0.016, PR= 1.65), physical activity (p=0.000, PR= 4.68), stress (p=0.000, PR= 2.30), and activity at the Integrated Development Post for non-communicable diseases (p=0.005, PR= 1.80) were related to cardiorespiratory fitness. The most dominant variables on cardiorespiratory fitness in DM hajj pilgrims were physical activity and stress variables controlled by age and gender. Conclusion: There is a relationship between age, gender, BMI, physical activity, stress and activity at the Integrated Development Post for Non-Communicable Diseases with cardiorespiratory fitness in DM hajj pilgrims. However, the most dominant is physical activity and stress which are controlled by age and gender. Keywords: Biopsychosocial; Cardiorespiratory; Diabetes Mellitus; Fitness; Hajj Pilgrim. Pendahuluan: Diabetes Mellitus (DM) berkaitan erat dengan penurunan kebugaran kardiorespirasi dan gangguan olahraga. DM merupakan penyakit tertinggi kedua setelah hipertensi pada jemaah haji di Kabupaten Blora. Status kebugaran kardiorespirasi pada jamaah haji di Kabupaten Blora tahun 2023 sebagian besar dengan kategori cukup (49.6%) dan kategori kurang (30.4%).Mengingat pentingnya kebugaran kardiorespirasi pada jemaah haji dengan DM, perlu dilakukan pendekatan yang mampu mengkaji berbagai faktor yang berhubungan dengan kebugaran kardiorespirasi melalui pendekatan biopsikososial. Tujuan: Untuk menganalisis determinan biopsikososial terhadap kebugaran kardiorespirasi pada jemaah haji dengan DM. Metode: Penelitian desain cross sectional, digunakan untuk mengkaji faktor biopsikososial terhadap kebugaran kardiorespirasi. Penelitian ini dilakukan di Kabupaten Blora pada bulan Februari-April 2024. Teknik pengambilan sampel menggunakan purposive sampling, besar sampel dihitung dengan rumus Slovin dan berdasarkan justifikasi peneliti diambil total sampling sebanyak 119 responden. Kriteria inklusi yaitu mampu berkomunikasi dengan baik, terdiagnosis DM oleh dokter, dan hasil laboratorium (GDS, GDP dan HBA1c). Analisis data menggunakan univariat, bivariat (chi-square dan regresi logistik), dan multivariat. Hasil: Sebagian besar responden (47.1%) mempunyai kebugaran kardiorespirasi kurang (tidak bugar). Hasil uji bivariat menunjukkan variabel umur (p=0.035, PR= 1.57), jenis kelamin (p=0.044, PR= 1.56), IMT (p=0.016, PR= 1.65), aktivitas fisik (p=0.000, PR= 4.68), stres (p=0.000, PR= 2.30), dan keaktifan dalam posbindu PTM (p=0.005, PR= 1.80) berhubungan dengan kebugaran kardiorespirasi. Variabel yang paling dominan terhadap kebugaran kardiorespirasi pada jemaah haji dengan DM adalah variabel aktivitas fisik dan stres yang dikontrol dengan umur dan jenis kelamin. Simpulan: Terdapat hubungan antara usia, jenis kelamin, IMT, aktivitas fisik, stres dan aktivitas di Pos Pembinaan Terpadu Penyakit Tidak Menular dengan kebugaran kardiorespirasi pada jemaah haji DM. Namun yang paling dominan adalah aktivitas fisik dan stres yang dikontrol oleh usia dan jenis kelamin. Kata Kunci: Biopsikososial; Diabetes Mellitus; Jemaah Haji; Kardiorespirasi; Kebugaran.